Design and analysis of optical metropolitan networks - Lian, Ziwen (2008)
An innovative network scheme called optical Resilient Ethernet Ring (RER) based on 10GbE technology has been designed and analysed with the motivation of adapting Ethernet technology from LANs to MANs.